New finds of the Carboniferous cephalopods on the territory of Ukraine - Vitaly Dernov (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2021)
Formulation of the problem. Carboniferous sediments are widespread in Ukraine. Cephalopods remains are not rare in these deposits. However, they are poorly studied. Cephalopods have great importance for the dismemberment and correlation of Carboniferous sediments, as well as for paleogeographic reconstructions. For this reason, their study is very relevant.